The Advocate’s Archive: Walter Rudnicki and the Fight for Indigenous Rights in Canada, 1955–2010 - Linden, Amanda (Archivaria, 2018)
This article explores the significant contribution that Walter Rudnicki (1925–2010) made to the pursuit of social justice for Indigenous people in Canada through his use of archival records. Rudnicki took on the role of archivist by acquiring, organizing, disseminating, and keeping records that document government–Indigenous relations. Totalling 90.25 metres in extent, the Walter Rudnicki Fonds at the University of Manitoba Archives & Special Collections is an impressive private collection amassed in order to make injustice visible. As a federal public servant working to develop innovative policies with Indigenous people between the 1950s and 1970s, Rudnicki had bitter personal experience with the ways that the Government of Canada’s practices regarding document creation and access to records thwarted Indigenous aims. Thereafter, he stressed that accessing and archiving records must play an indispensable role in protecting Indigenous peoples’ interests. He spent the rest of his life creating and employing an archive that would be used in advocacy for Indigenous rights. RÉSUMÉ Cet article explore la contribution importante de Walter Rudnicki (1925–2010) dans la recherche de justice sociale pour les peuples autochtones au Canada par son utilisation de documents d’archives. Rudnicki s’est attribué le rôle d’archiviste en faisant l’acquisition, le classement, la diffusion et la sauvegarde de documents d’archives qui décrivent les relations entre le gouvernement et les autochtones. D’une étendue de 90,25 mètres, le fonds Walter Rudnicki, conservé aux Archives et collections spéciales de la University of Manitoba, est une impressionnante collection privée amassée dans le but de rendre l’injustice visible. En tant que fonctionnaire fédéral qui travaillait au développement de politiques innovatrices avec les populations autochtones entre les années 1950 et les années 1970, Rudnicki a connu des expériences personnelles amères avec les façons dont les pratiques du Gouvernement du Canada en matière de création et d’accès aux documents ont contrecarré les visées des populations autochtones. Ensuite, il a insisté sur le fait que l’accès et l’archivage de documents doit jouer un rôle indispensable dans la protection des intérêts des populations autochtones. Il a passé le reste de sa vie à créer et à utiliser des archives qui serviraient à la défense des droits autochtones.